The human growth hormone gene family: structure and evolution of the chromosomal locus. - Barsh, G S (1983)
The structure of the human growth hormone gene cluster has been determined over a 78 kilobase region of DNA by the study of two overlapping cosmids. There are two growth hormone genes interspersed with three chorionic somatomammotropin genes, all in the same transcriptional orientation. One of the growth hormone genes lies in an active chromatin conformation in the pituitary and at least one of the chorionic somatomammotropin genes lies in an active chromatin conformation in the placenta. The two groups of genes are highly homologous throughout their 5' flanking and coding sequences, but diverge in their 3' flanking regions which raises the paradox of how genes so similar in structural and flanking sequences can be so differentially regulated. Analysis of the sequences of the genes and identification of at least three different classes of duplication units interspersed throughout the five gene cluster suggests that the cluster evolved quite recently and that the mechanism of gene duplication involved homologous but unequal exchange between middle repetitive elements of the Alu family.